PROLIFERATION RESISTANCE ASSESSMENT OF INDONESIAN 10-MWT RDE EXPERIMENTAL POWER REACTOR USING INPRO METHODOLOGY - Bening Farawan; Mohamad Sukron Fajrin Husein; Agus Sunarto; Arief Sasongko Adhi (website, 2020)
PROLIFERATION RESISTANCE ASSESSMENT OF INDONESIAN 10-MWT RDE EXPERIMENTAL POWER REACTOR USING INPRO METHODOLOGY. Assessment of proliferation resistance (PR) for 10-MWt RDE has been conducted to verify the RDE safeguards desain. Proliferation resistance (PR) is a parameter that can be used to measure the ability of a facility to implement safeguards (safeguardability). Safeguards is every technical measure used to ensure that every nuclear material in a facility is used as declared and only for welfare. Proliferation resistance of 10-MWt RDE has been assessed with INPRO methodology. The areas assessed were specific to intrinsic features of RDE, which consist of the attractiveness of nuclear material and technology and also detectability and chances of diversion of the nuclear material. This assessment concludes that the 10-MWt RDE has strong proliferation resistance, which indicates that the facility has small ability to diverse nuclear material and will less likely be used to proliferate nuclear weapon.Keywords: Proliferation Resistance, Safeguards, INPRO Methodology.